Experimental demonstration of dual-polarization multiplexed optical phased array empowered by inverse design - Kim Jae-Yong; Lee Seungsoo; Hong Seokjin; Neseli Berkay; Choi Seungyoon; Park Hyo-Hoon; Kurt Hamza (Nanophotonics, 2025)
This paper presents a dual-polarization multiplexed optical phased array (OPA) implemented on a 220 nm silicon-on-insulator (SOI) platform, enabling continuous beam steering across TE and TM modes. While effectively guiding TE- and TM-polarized light, the proposed OPA on this platform faces the challenge of overcoming the intrinsically high effective refractive index disparity between the two modes upon radiation from the grating antenna. To mitigate this challenge, key OPA components – polarization beam combiner, polarization-independent beam splitter, and index-modulated pixelized grating antenna – were optimized using inverse design methods and integrated, enabling efficient and seamless beam steering across both polarizations. With a 100 nm wavelength tuning range and dual-polarization operation, the fabricated 64-channel OPA achieves a notable longitudinal beam steering range of 34.9° across the TE and TM modes, along with full 2-D beam steering capability. The experimental results confirm the effectiveness of the proposed approach, highlighting its potential for advancing the next-generation LiDAR and optical wireless communication systems.